Nivel de competitividad en el Comercial Su Economía, ubicado en la Parroquia San Juan, periodo 2022. - Tomalá Chilan, José Antonio (2023)
The case study on the level of competitiveness of the commercial "Your Economy" reveals a series of administrative problems that have affected its performance in the market. Through a SWOT analysis and an EFE analysis that allow us to evaluate the level of competitiveness of the company “YOUR ECONOMY”, observing the processes and productivity it has to subsequently issue an interpretive report. Additionally, identify various areas of improvement and opportunities that could drive the future success of the business. In terms of weaknesses, "Su Economía" faces challenges in internal management, including a lack of efficiency in administrative processes and a lack of adaptation to new technological trends. Regarding the way of investigating, the integrated quality management system method was applied because the objective of this system is to achieve more efficient and effective management, improving customer satisfaction, process efficiency, cost reduction and continuous improvement. As a result, there are several key opportunities in the business that could be exploited. Firstly, the implementation of payments through cards and the creation of a website would attract a broader group of customers. Also the introduction of new brands to the premises and geographical expansion could diversify the offer and increase the customer base. In conclusion, innovation, service quality, customer service and alliances can be useful tools to differentiate and stand out in a competitive market.